Early evidence of the development of primary care networks in England: a rapid evaluation study - Judith Smith; Sarah Parkinson; Amelia Harshfield; Manbinder Sidhu (National Institute for Health Research, 2020)
Background: Primary care networks are groups of general practices brought together in July 2019 to develop new services in response to NHS England/Improvement policy using a shared budget. This study examined the early implementation of primary care networks, especially what has helped or hindered progress, how they operate in relation to pre-existing collaborations, and issues for rural networks. Objective: To produce early evidence about the development of primary care networks to inform policy for their future development. Our research questions were to investigate 1) the contextual background of primary care networks; 2) the rationale for general practices to enter into collaborations; 3) the early learning from establishing primary care networks; 4) barriers to and facilitators of effective collaboration across GP practices; and, 5) the likely future progress of primary care networks in the English NHS, including in light of Covid-19. Design: A qualitative cross-comparative case study evaluation comprised of four work packages: Results: Primary care networks have been implemented in a timely manner and have established a range of new local health services. Previous GP collaborations provide much-needed support in terms of management, leadership and infrastructure, although they can be a source of tension within networks where interests, goals and ways of working do not align.: Reasons for collaborative working typically focus on the sustainability of primary care and a desire for better integrated services, although those cited as the basis for joining primary care networks were mostly related to policy and financial incentives. Early evidence reveals operational success in establishing organisational structures, recruiting to new roles, and providing services as required by the national specification.: Effective management and leadership, particularly with respect to having a committed clinical director, and constructive relationships between primary care networks and clinical commissioning groups, are important in ensuring success. In rural areas there was some perceived lack of fit with aspects of the primary care network specification, alongside existing challenges of providing primary care to rural populations. Limitations: Arranging and completing interviews proved difficult given the workload associated with implementing networks and wider time pressures. Following the onset of the Covid-19 pandemic, the team was unable to undertake planned face-to-face workshops to explore findings. Given that primary care networks were in their first year of operation at the time of this evaluation, we were cautious in drawing definitive conclusions. Conclusions: Key lessons focus on: Future work: Evaluating the impact and effectiveness of primary care networks using quantitative and qualitative measures; undertaking research in both rural and urban areas, exploring the extent to which this context is significant; the cost and effectiveness of sustaining and extending leadership and management support within primary care networks; and understanding the relationships between primary care networks and the wider health and care system. Study registration: Ethical approval from the University of Birmingham Research Ethics Committee (ERN_13-1085AP34). Rapid Evidence Assessment protocol registered with PROSPERO (CRD42018110790) Funding: This project was funded by the National Institute of Health Research (NIHR) Health Services and Delivery Research programme (16/138/31 - Birmingham, RAND and Cambridge Evaluation Centre).